A Structural validity study of students’ attitudes towards statistics: An initial empirical investigation (Kajian keesahan struktur ke atas sikap pelajar terhadap statistik: suatu kajian empirikal permulaan) - Hairulliza Mohamad Judi; Hazura Mohamed; Noraidah Sahari @Ashaari; Tengku Siti Meriam Tengku Wook (Penerbit Universiti Kebangsaan Malaysia, 2011)
﻿Previous studies have shown that students’ positive attitudes towards statistics are as important as good teaching and learning method in a course in statistics. Both are required for students to achieve good grade in the course. The objective of this study is to test the structural relationship of attitudes towards statistics using the Survey of Attitudes towards Statistics© or SATS© instrument among a sample of students in Universiti Kebangsaan Malaysia (UKM). The instrument comprises of six components that measure attitude i.e. affect, cognitive, value, difficulty, effort and interest. A survey was conducted among 102 first year students in the Faculty of Information Science and Technology of UKM to assess early attitudes towards statistics. The model involving six components which describe attitudes towards statistics is found to be adequate. The relationship between components is also investigated and discussed.